2006
DOI: 10.1177/153857440604000305
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Distribution of Lower Extremity Deep Vein Thrombosis in Rehabilitation Patients: Implications for Screening

Abstract: Patients admitted to in-patient rehabilitation programs have an increased risk for developing deep venous thrombosis (DVT). However, the utility of screening for lower extremity DVT using duplex ultrasound in this high-risk population is not well characterized. The purpose of this study is to identify whether or not screening lower-extremity duplex exams are indicated in this high-risk population. Screening lower extremity duplex exams were performed on all patients admitted to the rehabilitation center at Mt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…14,15,17,18 This omission is mirrored in other reviews 2,20,23 and limited our ability to derive a reliable pooled estimate for the effect of anticoagulation on this outcome. Treatment with a vitamin K antagonist or heparin may result in major bleeding in 3% to 5% of patients per year.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…14,15,17,18 This omission is mirrored in other reviews 2,20,23 and limited our ability to derive a reliable pooled estimate for the effect of anticoagulation on this outcome. Treatment with a vitamin K antagonist or heparin may result in major bleeding in 3% to 5% of patients per year.…”
Section: Discussionmentioning
confidence: 73%
“…Many were investigating the relationships between anticoagulation therapy and the treatment of any DVT (including proximal), 14 PE,13 or duplex surveillance. 16,18 Therefore, we extracted data pertinent to our review from these larger populations, resulting in a small number of included patients (n ϭ 200) and a very low event rate overall (n ϭ 5). In addition, although our sensitivity and subgroup analysis was limited, it revealed that PE was highly determined by the included studies in the pooled …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A recent study detected lower extremity DVT in 34% of patients, and 23% of patients displayed isolated calf vein thrombosis among patients admitted to inpatient rehabilitation programs. 8 Several previous studies have suggested that DVT is less frequent among Asians than among Caucasians. 9 De Silva et al, 10 however, reported that DVT following ischemic stroke among Asians is common and associated with poor functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of symptoms to predict PE has led to the use of objective methods of examination, including screening compression ultrasound (CUS), which has become the primary non-invasive diagnostic method for DVT [6]. One retrospective study [7] found that one-third of a group of rehabilitation patients had DVT at admission to the rehabilitation unit. These authors proposed that such patients should have ultrasound screening at admission to detect DVT, though there is no evidence that screening ultrasound reduces clinically important outcomes, including PE [8].…”
mentioning
confidence: 99%